Sumber Energi Terbarukan dan Pupuk Organik dari Limbah Kotoran Sapi - Mulyatun, Mulyatun (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2016)
In order to meet households energy needs, one of the groundbreaking efforts that needs to be done is to implement appropriate technology training in utilization of cow manure waste by recycling it into biogas and organic fertilizer. Animal husbandry in Bambankerep Sub-District of Ngaliyan, Semarang City, are sufficiently developed, however, the use of livestock manure has not been optimal, whereas livestock manure can be used as raw material to produce renewable energy in the form of biogas and organic fertilizer. Furthermore, Limited knowledge and skills of the people in Bambankerep sub-district in the utilization of cow manure waste by recycling it into biogas and organic fertilizer have become the main problem. Steps performed in Community service programs are as follow (1) Socialization of recycling livestock waste into a blessing; (2) training, (3) Monitoring and outreaching. The impact generated from this community service programs, among others are: (1) raising public awareness in the utilization of cow manure waste for biogas alternative energy, (2) increasing knowledge and skills of people in processing cow manure into energy and fertilizer, (3) growing number of business groups in cow manure organic fertilizer processing that are expected can improve the welfare of the people in Bambankerep sub-district, Mijen, Semarang City.Â Dalam rangka pemenuhan keperluan energi rumah tangga, salah satu upaya terobosan yang perlu dilakukan adalah melaksanakan pelatihan teknologi tepat guna pemanfaatan limbah kotoran sapi menjadi biogas dan pupuk organik. Usaha peternakan di Kelurahan Bambankerep, Ngaliyan Semarang cukup berkembang, tapi pemanfaatan kotoran ternak selama ini belum optimal, padahal kotoran ternak dapat dijadikan sebagai bahan baku untuk menghasilkan energi terbarukan dalam bentuk biogas dan pupuk organik. Keterbatasannya pengetahuan dan keterampilan yang dimiliki masyarakat di Kelurahan Bambankerep mengolah limbah kotoran sapai menjadi biogas dan pupuk organik menjadi permasalahn utama. Tahapan program pengabdian masyarakat yang dilakukan adalah: (1) Sosialisai pemanfaatan limbah kotoran hewan menjadi berkah; (2) pelatihan; (3) Monitoring dan Pendampingan. Dampak yang dihasilkan dari program pengabdian masyarakat ini antara lain: (1) meningkatkan kesadaran masyarakat untuk memanfaatkan limbah kotoran sapi untuk energi alternatif biogas, (2) meningkatnya pengetahuan dan ketrampilan masyarakat bidang pengolahan kotoran sapi menjadi energi dan pupuk, (3) tumbuhnya kelompok usaha pengolahan pupuk organik dari kotoran sapi sehingga diharapkan dapat meningkatkan kesejahteraan masyarakat Kelurahan Bambankerep Ngaliyan Semarang.